(untitled) (Journal of the Entomological Research Society, 2019)
We investigated that the effects of oxyclozanide on survival rate, development time, adult longevity and the amount of total protein (TP) in different developmental stages (7th-instars larvae, pupae and adult) of greater wax moth Galleria mellonella L. First-instar larvae of insects were reared on 0.003, 0.03 and 0.3 g oxyclozanide in 100 g artificial diets. When compared to all tested concentrations of oxyclozanide and control diet without oxyclozanide, it was confirmed that this anthelmintic drug significantly reduced survival rate of 7th-instar larval stage, pupal and adult stage of G. mellonella. While 7th-instars larval rate is 91.25 Â± 6.21 % in the control diet without oxyclozanide, this rate has been determined 28.75 Â± 3.24 % in the 0.3 % concentration of oxyclozanide. TP of the insect increased in response to all concentration of oxyclozanide in comparison to control diet. This considerable increase was expressed almost two-fold especially at the 0.003 and 0.03 % of oxyclozanide concentrations in all developmental stages. The results obtained from this research support that the oxyclozanide has effects on the survival, development, adult longevity and TP of the insect.